Bone Marrow Mesenchymal Stem Cell-Derived Exosomal miR-25 Regulates the Ubiquitination and Degradation of Runx2 by SMURF1 to Promote Fracture Healing in Mice - Jiang, Yikun; Zhang, Jun; Li, Zhengwei; Jia, Guoliang (Frontiers in Medicine, 2020)
Recent evidence has demonstrated that mesenchymal stem cells (MSCs) can release a large number of functionally specific microRNA (miRNA) microvesicles that play a role in promoting osteogenic differentiation, but the specific mechanism is not yet clear. Under such context, this study aims to elucidate the mechanism of bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exo) promoting fracture healing in mice. We isolated and identified the BMSC-Exo. Bioinformatics analysis predicted high expression of miRNA in exosomes and verified the transfer of miR-25 in exosomes by immunofluorescence. Targeting relationship between miR-25 and Smad ubiquitination regulatory factor-1 (SMURF1) was predicted and verified by dual-luciferase reporter gene assay. Immunoprecipitation and protein stability assays were used to detect Runt-related transcription factor 2 (Runx2) ubiquitination and the effect of SMURF1 on Runx2 ubiquitination, respectively. The effect of miR-25 in BMSC-Exo on fracture healing in mice was assessed using X-ray imaging. alkaline phosphatase, alizarin red staining, EdU, CCK-8, and Transwell were used to evaluate the effects of exosomes transferred miR-25 on osteogenic differentiation, proliferation and migration of osteoblasts. Bioinformatics analysis predicted that miR-25 expression in exosomes increased significantly. Moreover, the targeted regulation of SMURF1 by miR-25 was verified. SMURF1 inhibited Runx2 protein expression by promoting ubiquitination degradation of Runx2. Notably, miR-25 secreted by BMSC-Exo can accelerate osteogenic differentiation, proliferation and migration of osteoblasts through SMURF1/Runx2 axis. Our results demonstrate that miR-25 in BMSC-Exo regulates the ubiquitination degradation of Runx2 by SMURF1 to promote fracture healing in mice.